Describing the Semantic Field of Beauty based on COBUILD: (Pemaknaan Medan Kecantikan Berasaskan Amalan Cobuild) (Jurnal Bahasa, 2018)
This article presents is a study which applies COBUILD (Collins Birmingham University International Language Database) to describe the semantics field of "beauty" for the monolingual Malay language dictionary. The COBUILD approach is chosen as it provides meaning in the form of description. This form explains meaning in a similar way to Standard Malay. This approach is different from the lexicographical practices applied in the contemporary monolingual dictionary, which uses the "compression" form. 18 entries of the semantics field of beauty were examined. This study presents two objectives, firstly, the application of COBUILD in describing the semantic field of beauty and secondly, to look at collocations as a meaning differentiator. 33 meanings were gathered from 18 entries through the computerized corpus data of Dewan Bahasa and dan Pustaka. From these meanings, 15 groups of meaning were grouped, whether from the same entry or a different one. The similarities and differences are defined through collocations examined from the concordance lines.Keywords: COBUILD, semantics field of beauty, collocation, corpus data, monolingual dictionary